Effectiveness of Group Value Clarification Counseling to Minimize Social Anxiety Due to Cyberbullying Behavior - Akhmad Fajar Prasetya; I Made Sonny Gunawan; M. Zuhdi Zainul Majd (Universitas Negeri Semarang, 2021)
The purpose of this study was to determine the effectiveness of group counseling values clarification modeling techniques using short videos on social anxiety due to cyberbullying in students. This study uses an experimental design of one group pre-test and post-test control design. The subjects in this study were 12 students who attended SMA Negeri 3 Mataram, Indonesia. Data were collected using the Social Anxiety Scale. Data analysis using ANOVA statistics. The results of this study revealed that the values clarification group counseling with modeling techniques was effective in minimizing students' social anxiety. In addition, data obtained that the level of social anxiety of female students is higher than that of male students.